?PROLONGING OF SHELF LIFE OF FRESH VEGETABLES WITH THE HELP OF EMULSION - SHAIKH, IFTIKHAR ALl; ASLAM, M.; ARSHAD, M.; ADIL, RAZIA (Biological Sciences - PJSIR, 1995)
Attempts were made in the present investigation to develop a suitable emulsion and easy method for extending the shelf life of vegetables. Vegetable oil based emulsion developed after necessary trial was applied on different vegetables. Change in moisture, respiration and appearance of vegetables treated with emulsion were determined and compared with those of untreated vegetables. It was observed that shelf life of vegetables which can normally be kept for three days, can be extended to three to five days with the help of emulsion.